Honeycomb filter comprising activated carbon and method of making same
By using high nitrogen content activated carbon in honeycomb filters, the problem of existing filters being difficult to efficiently capture carbon dioxide is solved, achieving more efficient greenhouse gas capture and longer-lasting filter performance.
Patent Information
- Application Number
- CN202380065980.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-28
- Filing Date
- 2023-09-18
- Publication Date
- 2025-04-25
AI Technical Summary
Existing filters are difficult to capture carbon dioxide efficiently, making it difficult to solve greenhouse gas emissions problems.
A honeycomb filter containing activated carbon with high nitrogen content is used. The filter distributes activated carbon through the porous channel wall, and uses nitrogen atoms to combine with carbon dioxide gas molecules to achieve more efficient adsorption.
It improves the carbon dioxide adsorption capacity of the honeycomb filter, enhances the capture efficiency of greenhouse gases, and extends the regeneration cycle life of the filter.
Smart Images

Figure CN119894584A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of priority under 35 U.S.C. §119 to U.S. Provisional Application No. 63 / 410,760, filed on September 28, 2022, the contents of which are incorporated herein by reference in their entirety. Technical Field
[0003] Embodiments of the present disclosure generally relate to separation devices. More specifically, embodiments of the present disclosure relate to filters and methods of making filters. Background Art
[0004] Greenhouse gas emissions are associated with increases in global average temperatures and have potentially harmful effects on ecosystems. In addition, large amounts of carbon dioxide emissions contribute to the greenhouse gas effect, at least in part due to the burning of fossil fuels. Therefore, the capture of carbon dioxide has been studied worldwide to mitigate the amount of these greenhouse gases entering the atmosphere. One such method of capturing carbon dioxide is by filtering process gases including carbon dioxide. Therefore, there is a need for improved filters that can capture carbon dioxide. Summary of the invention
[0005] According to one embodiment described herein, a honeycomb filter may include a porous honeycomb body containing activated carbon, the porous honeycomb body having a plurality of parallel cell channels defined by porous channel walls that traverse the porous honeycomb body from an upstream inlet end to a downstream outlet end, wherein: the activated carbon is distributed throughout the porous channel walls; and the activated carbon contains 1 wt % to 50 wt % nitrogen, based on the total weight of the activated carbon.
[0006] According to another embodiment described herein, a method for manufacturing a honeycomb filter may include: forming a formable honeycomb precursor composition comprising a cross-linked resin, wherein the cross-linked resin comprises 0.5 wt % to 4 wt % nitrogen, based on the total weight of the cross-linked resin; forming the honeycomb precursor composition to form a honeycomb green body having a plurality of parallel cell channels defined by porous channel walls that cross the honeycomb green body from an upstream inlet end to a downstream outlet end; heat treating the honeycomb green body to carbonize the cross-linked resin and form a carbonized honeycomb green body; and activating the carbonized honeycomb green body to produce a honeycomb filter, wherein the honeycomb filter comprises an activated carbon honeycomb body having a plurality of parallel cell channels defined by porous channel walls that cross the honeycomb body from an upstream inlet end to a downstream outlet end, wherein the activated carbon honeycomb body comprises activated carbon that comprises 1 wt % to 50 wt % nitrogen, based on the total weight of the activated carbon.
[0007] According to another embodiment described herein, a method for manufacturing a honeycomb filter may include: forming a honeycomb precursor composition comprising a cross-linked resin, wherein the cross-linked resin comprises 0.5 wt % to 4 wt % nitrogen, based on the total weight of the cross-linked resin; heat treating the honeycomb precursor composition to carbonize the cross-linked resin and form a carbonized honeycomb precursor composition; activating the carbonized honeycomb precursor composition to produce an activated honeycomb precursor composition; and forming the activated honeycomb precursor composition to form a honeycomb filter, the honeycomb filter comprising an activated carbon honeycomb body having a plurality of parallel cell channels defined by porous channel walls that traverse the honeycomb body from an upstream inlet end to a downstream outlet end, wherein the activated carbon honeycomb body comprises activated carbon comprising 1 wt % to 50 wt % nitrogen, based on the total weight of the activated carbon.
[0008] Other features and advantages of the embodiments described herein are set forth in the detailed description, claims, and drawings.
[0009] The foregoing general description and the following detailed description provide various embodiments and provide an overall review or framework for understanding the nature and character of the claimed subject matter. The accompanying drawings provide a further understanding of the various embodiments and are incorporated into and constitute a part of this specification. The drawings and description explain the principles and operation of the claimed subject matter. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] The following detailed description of specific embodiments of the present disclosure may be best understood when read in conjunction with the following drawings, in which like structures are represented by like reference numerals, and in which:
[0011] Figure 1 is an elevation view of a honeycomb filter according to one or more embodiments described herein.
[0012] Reference will now be made in more detail to various embodiments, some of which are illustrated in the accompanying drawings. Wherever possible, the same reference numerals will be used throughout the drawings to refer to the same or like parts. DETAILED DESCRIPTION
[0013] Reference will now be made in more detail to various embodiments. The present disclosure relates to a honeycomb filter that may include activated carbon. Such a honeycomb filter may be operable to capture carbon dioxide in a process gas stream (e.g., an automobile exhaust stream). As described in detail herein, the honeycomb filter may include a porous wall, and the process gas may pass through the porous wall, resulting in separation of at least some carbon dioxide from the process gas stream.
[0014] According to embodiments described herein, the honeycomb may include activated carbon, wherein the activated carbon includes a relatively high nitrogen content (e.g., at least 1 wt. % nitrogen). It has been found that the use of such activated carbon having a relatively high nitrogen content can increase the carbon dioxide adsorption capacity of the honeycomb. Such filters and methods of making and using such filters are described in detail herein.
[0015] See also Figure 1 , showing a honeycomb filter 100 having a porous honeycomb body 101, which has: an inlet end 102, an outlet end 104, and a plurality of parallel cell channels 108 extending from the inlet end 102 to the outlet end 104, wherein the cell channels 108 are defined by porous channel walls 106 that traverse from the inlet end 102 to the outlet end 104. In one or more embodiments, the porous channel walls 106 can be configured so that the cell channels 108 have any cross-sectional shape, such as but not limited to: square, circular, elliptical, hexagonal or triangular cross-sectional shapes. In one or more embodiments, most to all of the cell channels 108 can have the same or similar cross-sectional shape and each cell channel 108 can share one or more porous channel walls 106 with adjacent cell channels 108, so that one cell channel 108 is parallel or nearly parallel to an adjacent cell channel 108, wherein this pattern can be repeated throughout the honeycomb filter 100.
[0016] In one or more embodiments, one or more cell channels 108 of the honeycomb filter 100 may have a plug 112. In some embodiments, the plug 112 present on the one or more cell channels 108 of the honeycomb filter 100 may be located at or near the inlet end 102 of the one or more cell channels 108 that are blocked. In some embodiments, a portion of the cell channels 108 on the outlet end 104 (but not corresponding to those on the inlet end 102) may also be blocked in a similar pattern. In some embodiments, each cell channel 108 is blocked at only one end. In some embodiments, the cell channels 108 are arranged so that every other hole on a given face is blocked in a checkered pattern, such as Figure 1 As shown further.
[0017] It will be appreciated that this plugging configuration achieves intimate contact between the fluid process stream and the porous channel walls 106 of the honeycomb filter 100. The fluid process stream can flow into the honeycomb filter 100 through the open cell channels 108 at the inlet end 102, then pass through the porous cell walls 106, and exit the porous honeycomb body 101 through the open cells at the outlet end 104. As described herein, the honeycomb filter 100 may be referred to as a "wall flow" structure because the flow path resulting from the alternating plugged cells requires that the fluid process stream being processed flow through the porous channel walls 106 before exiting the porous honeycomb body 101. In one embodiment, the percentage of open cell channels 108 of the honeycomb filter 100 compared to the total number of cell channels 108 can be 10% to 90%, for example: 20% to 90%, 30% to 90%, 40% to 90%, 50% to 90%, 60% to 90%, 70% to 90%, 80% to 90%, 20% to 80%, 30% to 70%, or 40% to 60%.
[0018] In one or more embodiments, the porous honeycomb body 101 may include activated carbon. As described herein, activated carbon may refer to a carbonaceous composition containing small, low-volume pores and a relatively high surface area that is operable to adsorb one or more pollutants. As described herein, in addition to carbon atoms, activated carbon may include other atoms, such as nitrogen. Generally speaking, nitrogen may be bonded to carbon atoms in the activated carbon.
[0019] In one or more embodiments, activated carbon may be distributed at least throughout the porous channel walls 106 of the porous honeycomb body 101, wherein the activated carbon may be distributed throughout or nearly throughout the porous honeycomb body 101. As described herein, activated carbon distributed throughout at least a portion of the porous channel walls 106 and / or throughout the porous honeycomb body 101 may represent activated carbon that is well distributed throughout or nearly throughout the solid porous channel walls 106 and / or porous honeycomb body 101 structure, as opposed to having activated carbon deposited only on one or more surfaces of the porous channel walls 106 and / or porous honeycomb body 101. For example, and as described in detail herein, the activated carbon may be distributed throughout the body 101 formed from a material having a relatively uniform distribution of activated carbon or a precursor of activated carbon.
[0020] In one or more embodiments, the activated carbon may include nitrogen. In one or more embodiments, the activated carbon of the porous honeycomb body 101 may include 1 wt % to 50 wt % nitrogen, based on the total weight of the activated carbon. For example, in one or more embodiments, the activated carbon of the porous honeycomb body 101 can include: 1 wt % to 50 wt % nitrogen, 5 wt % to 50 wt % nitrogen, 7.5 wt % to 50 wt % nitrogen, 10 wt % to 50 wt % nitrogen, 12.5 wt % to 50 wt % nitrogen, 15 wt % to 50 wt % nitrogen, 20 wt % to 50 wt % nitrogen, 25 wt % to 50 wt % nitrogen, 35 wt % to 50 wt % nitrogen, 1 wt % to 40 wt % nitrogen, 1 wt % to 30 wt % nitrogen, 1 wt % to 20 wt % nitrogen, 1 wt % to 10 wt % nitrogen, 5 wt % to 45 wt % nitrogen, 10 wt % to 45 wt % nitrogen, 15 wt % to 45 wt % nitrogen, 20 wt % to 45 wt % nitrogen, or 25 wt % to 40 wt % nitrogen, based on the total weight of the activated carbon.
[0021] Without being limited to any particular theory, it is believed that a higher nitrogen content (e.g., at least 1 wt. %) of the activated carbon can result in increased adsorption of one or more molecules of a gas stream that may pass through the honeycomb body 100, as compared to conventional filters that do not employ nitrogen-containing activated carbon. Specifically, it is believed that the activated carbon distributed throughout the porous channel walls 106 of the honeycomb filter 100 allows the nitrogen atoms of the activated carbon to better bind to one or more molecules of a gas stream that pass through the pores of the porous channel walls 106. In one or more embodiments, the nitrogen can effectively bind to carbon dioxide gas.
[0022] In addition, it is believed that the honeycomb filter structure having activated carbon containing 1 wt% to 50 wt% nitrogen distributed throughout the honeycomb body achieves close contact between the gas and the activated carbon (the activated carbon contains 1 wt% to 50 wt% nitrogen), thereby increasing the adsorption of one or more molecules of the gas flow passing through the filter, which is compared to a conventional filter that does not form a filter body with a nitrogen-containing compound distributed throughout. The porous honeycomb body described throughout is formed by a nitrogen-containing compound and a resin, so that the entire body of the honeycomb filter 100 has distributed activated carbon (the activated carbon contains 1 wt% to 50 wt% nitrogen). Therefore, this can also lead to the honeycomb filter 100 achieving a more durable ability to adsorb one or more molecules of the gas flow (such as carbon dioxide), because after multiple regeneration cycles, the nitrogen atoms will remain intact throughout the porous honeycomb body 101, compared to conventional filters that may deposit nitrogen-containing compounds on the surface of the filter, wherein these deposits will erode after multiple regeneration cycles. In addition, the entire porous honeycomb body 101 has distributed activated carbon, which contains 1 weight percent to 50 weight percent nitrogen, which enables this filter to remove adsorbed materials by electrical regeneration, which can enable the filter to withstand more regeneration cycles and result in a longer-lasting filter, compared to filters that undergo other conventional regeneration processes.
[0023] The activated carbon described herein may contain a total carbon content ranging from 10 wt % to 50 wt %, relative to the total weight of the activated carbon, for example, a total carbon content of 15 wt % to 50 wt %, 20 wt % to 50 wt %, 25 wt % to 50 wt %, 30 wt % to 50 wt %, 35 wt % to 50 wt %, 40 wt % to 50 wt %, 10 wt % to 45 wt %, 10 wt % to 40 wt %, 10 wt % to 35 wt %, 10 wt % to 30 wt %, 10 wt % to 25 wt %, 10 wt % to 20 wt %, 15 wt % to 45 wt %, 20 wt % to 40 wt %, or 25 wt % to 35 wt %, relative to the total weight of the activated carbon.
[0024] The honeycomb filter 100 described herein may also be characterized based on the pore microstructure and nanostructure of the honeycomb filter body. In one or more embodiments, the porous honeycomb body 101 (including the porous channel walls 106) may include micropores (e.g., pores with a diameter of 0.1 μm to 150 μm) and / or nanopores (e.g., pores with a diameter of 0.01 nm to 100 nm). The pores of the honeycomb filter body may be characterized as "interconnected," whereby the pores connect into other pores and / or the pores intersect with other pores to produce a tortuous network of porosity within the substrate. As will be appreciated by those skilled in the art, interconnected pores may help reduce undesirable back pressure levels that may form when a fluid process stream passes through the honeycomb filter 100.
[0025] In one or more embodiments, the porous honeycomb body 101 can have a cell channel density of 5 to 900 cell channels per square centimeter. For example, the porous honeycomb body 101 can have a cell channel density of 10 to 900 cell channels, 50 to 900 cell channels, 100 to 900 cell channels, 200 to 900 cell channels, 300 to 900 cell channels, 400 to 900 cell channels, 500 to 900 cell channels, or 100 to 900 cell channels. channels, 5 channels to 750 channels, 5 channels to 500 channels, 5 channels to 400 channels, 5 channels to 300 channels, 5 channels to 200 channels, 50 channels to 700 channels, 150 channels to 500 channels, or 200 channels to 400 channels, per square centimeter.
[0026] In one or more embodiments, the porous channel walls 106 of the cell channels 108 may have an average wall thickness of 0.001 cm to 0.15 cm. For example, the porous channel walls 106 of the cell channels 108 may have an average wall thickness of 0.005 cm to 0.15 cm, 0.01 cm to 0.15 cm, 0.05 cm to 0.15 cm, 0.1 cm to 0.15 cm, 0.001 cm to 0.1 cm, 0.001 cm to 0.05 cm, 0.001 cm to 0.01 cm, or 0.001 cm to 0.005 cm.
[0027] In one or more embodiments, the honeycomb filter bodies described herein may have a 750 m 2 / g to 2500m 2 For example, a honeycomb filter body may have a surface area of 1000 m 2 / g to 2500m 2 / g,1250m 2 / g to 2500m 2 / g,1500m 2 / g to 2500m 2 / g,1750m 2 / g to 2500m 2 / g,2000m 2 / g to 2500m 2 / g,2250m 2 / g to 2500m 2 / g,750m 2 / g to 2250m 2 / g,750m 2 / g to 2000m 2 / g,750m 2 / g to 1750m 2 / g,750m 2 / g to 1500m 2 / g,750m 2 / g to 1225m 2 / g,750m 2 / g to 1000m 2 / g,1000m 2 / g to 2000m 2 / g, or 1250m 2 / g to 1775m 2 / g.
[0028] According to other embodiments, carbon dioxide can be adsorbed by passing a gas containing carbon dioxide through one or more of the plurality of parallel channels of the honeycomb filter 100. In such embodiments, at least a portion of the gas passes through one or more porous channel walls, and at least a portion of the carbon dioxide from the gas is adsorbed onto the one or more porous channel walls. As described herein, adsorption can mean when one or more molecules in the gas (e.g., carbon dioxide) are bound to at least a portion of the honeycomb filter 100, wherein the one or more molecules in the gas (e.g., carbon dioxide) are bound to nitrogen atoms of the activated carbon.
[0029] As described herein, the honeycomb filter 100 described in the present application can be formed by various methods. According to one or more embodiments, the method for manufacturing the honeycomb filter 100 may include: forming a formable honeycomb precursor composition including a cross-linked resin; forming the honeycomb precursor composition to form a honeycomb green body; heat treating the honeycomb green body to carbonize the cross-linked resin and form a carbonized honeycomb green body; and activating the carbonized honeycomb green body to produce a honeycomb filter 100 including an activated carbon honeycomb body.
[0030] According to other embodiments, the manufacturing method of the honeycomb filter 100 may include: forming a honeycomb precursor composition containing a cross-linked resin; heat-treating the honeycomb precursor composition to carbonize the cross-linked resin and form a carbonized honeycomb precursor composition; activating the carbonized honeycomb precursor composition to produce an activated honeycomb precursor composition; and shaping the activated honeycomb precursor composition to form a honeycomb filter 100 containing an activated carbon honeycomb body.
[0031] According to other embodiments, the manufacturing method of the honeycomb filter 100 may include: forming a honeycomb precursor composition containing a cross-linked resin; heat-treating the honeycomb precursor composition to carbonize the cross-linked resin and form a carbonized honeycomb precursor composition; shaping the carbonized honeycomb precursor composition to form a shaped carbonized honeycomb precursor composition having a body; and activating the shaped carbonized honeycomb precursor composition to produce a honeycomb filter 100 having an activated carbon honeycomb body.
[0032] As used herein, cross-linked resin refers to a substance containing polymerized carbon, which is converted into continuous structural carbon after heating. In one embodiment, the cross-linked resin can be a synthetic resin in the form of a solution or a low-viscosity liquid at ambient temperature. Alternatively, the cross-linked resin can be solid under ambient conditions and can be liquefied by heating or other means. Thus, the cross-linked resin as used herein includes any liquid or liquefiable carbonaceous material. Examples of cross-linked resins include thermosetting resins and thermoplastic resins (e.g., polyvinylidene chloride, polyvinyl chloride, and polyvinyl alcohol, etc.). In addition, in one embodiment, a cross-linked resin (e.g., a thermosetting resin) with a lower viscosity can have a viscosity range of about 50 to 100 centipoise. In other embodiments, any high carbon yield resin can be used. As used herein, high carbon yield means that about 10% of the initial weight of the resin is converted into carbon after carbonization.
[0033] In one or more embodiments, the cross-linked resin may be one or more nitrogen-containing resins. For example, in one or more embodiments, the cross-linked resin may be a resin comprising cross-linked nitrogen-containing polymer chains, wherein the nitrogen-containing polymer chains are formed by polymerization of nitrogen-containing compounds (e.g., aminophenols, nitrophenols, melamines and / or primary amines, secondary amines, tertiary amines (e.g., linear polyethyleneimine, branched polyethyleneimine, cross-linked polyethyleneimine, etc.). For example, in one embodiment, aminophenols may be combined with one or more reactants (e.g., formaldehyde) to form nitrogen-containing polymer chains, wherein the nitrogen-containing polymer chains further interact and cross-link to produce aminophenol-based resins. In another example, melamine may be combined with one or more reactants (e.g., formaldehyde) to form nitrogen-containing polymer chains, wherein the nitrogen-containing polymer chains further interact and cross-link to produce melamine-based resins. It is to be understood that nitrogen-containing compounds may be combined and reacted with various other reactants and one or more solvents under operating conditions of different cross-linking modes of the cross-linked polymer chains formed by the cross-linked resin.
[0034] In one or more embodiments, the cross-linked resin may contain 0.5 wt % to 4 wt % nitrogen, based on the total weight of the cross-linked resin. For example, the cross-linked resin may contain: 0.5 wt % to 3.5 wt % nitrogen, 0.5 wt % to 3 wt % nitrogen, 0.5 wt % to 2.5 wt % nitrogen, 0.5 wt % to 2 wt % nitrogen, 0.5 wt % to 1.5 wt % nitrogen, 1 wt % to 4 wt % nitrogen, 1.5 wt % to 4 wt % nitrogen, 2 wt % to 4 wt % nitrogen, 2.5 wt % to 4 wt % nitrogen, 3 wt % to 4 wt % nitrogen, 1 wt % to 3 wt % nitrogen, or 1.5 wt % to 2.5 wt % nitrogen, based on the total weight of the cross-linked resin.
[0035] In another embodiment, the cross-linked resin may include a phenolic resin or a furan resin. The phenolic resin may have a low viscosity, a high carbon yield, and a high degree of crosslinking after curing relative to other precursors, and may have a relatively low cost. The example of a phenolic resin may be a resol, such as: 43250 plyophen resin, 43290 of Occidental Chemical Corporation, and the Durite resol of Borden Chemical Company. The example of a furan liquid resin is the Furcab-LP of QO Chemicals Inc. (QOChemicals Inc). An exemplary solid resin may be a solid phenolic resin or a novolac resin.
[0036] The honeycomb precursor composition comprising a crosslinked resin may optionally be mixed with one or more binders, fillers and / or forming aids. Binders refer to materials used to form a copolymeric whole as a means of providing structural stability. Fillers refer to particles (e.g., plastics, composites, concrete) added to a resin or binder that can improve the specific properties of the overall composition. Forming aids may represent any additive added to a resin to help facilitate resin processing. Binders that can be used are plasticized temporary organic binders, such as cellulose ethers. Typical cellulose ethers include: methylcellulose, ethyl hydroxyethyl cellulose, hydroxybutyl cellulose, hydroxybutyl methyl cellulose, hydroxyethyl cellulose, hydroxymethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl methyl cellulose, sodium carboxymethyl cellulose, and mixtures thereof. In addition, methylcellulose and / or methylcellulose derivatives may be used together with methylcellulose, hydroxypropyl methyl cellulose, or a combination of these.
[0037] Fillers that can also be used in the honeycomb precursor composition include: natural and synthetic, hydrophobic and hydrophilic, fibrous and non-fibrous, and carbonizable and non-carbonizable fillers. For example, some natural fillers can be softwoods, such as pine, fir, redwood, etc.; hardwoods, such as ash, beech, birch, maple, oak, etc.; wood chips, shell fibers, such as almond shells, coconut shells, apricot shells, peanut shells, hickory shells, walnut shells, etc.; cotton fibers, such as cotton chips, cotton fabrics, cellulose fibers, cotton seed fibers; chopped plant fibers, such as hemp fibers, coconut fibers, jute fibers, sisal fibers and other materials such as corn cobs, citrus pulp (dry), soybean meal, peat moss, wheat flour, wool fibers, corn, potatoes, rice, cassava flour, coal powder, activated carbon powder, etc. Some synthetic materials can be regenerated cellulose, rayon fabrics, cellophane, etc. In addition, partially or fully cured resin powders can also be added as carbonizable fillers.
[0038] Examples of carbonizable fillers may be cellulose, cotton, wood and sisal or combinations of these, all of which may be in the form of fibers. An example of a carbonizable fiber filler is cellulose fiber provided by International Filler Corporation, North Tonawanda, NY. This material has the following sieve analysis: 1-2% retained at 40 mesh (420 microns), 90-95% passed through 100 mesh (149 microns), and 55-60% passed through 200 mesh (74 microns).
[0039] Inorganic fillers that can be used include: oxygen-containing minerals or salts thereof, such as clays, zeolites, talc, etc., carbonates such as calcium carbonate, aluminosilicates such as kaolin (aluminosilicate clay), fly ash (aluminosilicate ash obtained after burning coal in power plants), silicates such as wollastonite (calcium metasilicate), titanates, zirconates, zirconia, zirconium oxide spinel, magnesium aluminum silicate, mullite, alumina, alumina trihydrate, boehmite, spinel, feldspar, attapulgite and aluminosilicate fibers, cordierite powder, etc. Some other examples of inorganic fillers are cordierite powder, talc, clay and aluminosilicate fibers, such as those provided by Carborundum Co. Niagara Falls, NY under the trade name Fiberfax, and combinations of these. Fiberfax aluminosilicate fibers can measure about 2-6 microns in diameter and about 20-50 microns in length. Other examples of inorganic fillers are various carbides such as silicon carbide, titanium carbide, aluminum carbide, zirconium carbide, boron carbide and aluminum titanium carbide; carbonates or carbonate-containing minerals such as baking soda, nahcolite, calcite, sodium carbonate and calcite; and nitrides such as silicon nitride.
[0040] Hydrophobic organic fillers can also provide additional support for the formed structure and introduce wall porosity upon carbonization, as these fillers generally leave less carbon residue. Some hydrophobic organic fillers can be: polyacrylonitrile fibers, polyester fibers (chips), nylon fibers, polypropylene fibers (chips) or powders, acrylic fibers or powders, aramid fibers, polyvinyl alcohol, etc.
[0041] Other binders and fillers that may be used in the present disclosure are disclosed and described in U.S. Patent No. 5,820,967, the entire disclosure of which is incorporated herein by reference.
[0042] Optionally, a forming aid (e.g., an extrusion aid) may also be included in the honeycomb precursor composition. To this end, the forming aid may include soap, fatty acids such as oleic acid, linoleic acid, etc., polyoxyethylene stearate, etc., or a combination thereof. In some embodiments, sodium stearate may be used as a forming aid. The optimal amount of the optional forming aid and / or extrusion aid will depend on the composition and the binder. Other additives that may be useful for improving the extrusion and curing characteristics of the honeycomb precursor composition may be phosphoric acid and oil. Phosphoric acid can improve the curing rate and increase the adsorption capacity. It is used in the honeycomb precursor composition mixture at about 0.1 wt % to 5 wt %.
[0043] In addition, adding oil can help extrusion, and can cause the surface area and porosity to increase. For this reason, optional oil can be added in an amount of about 0.1% by weight to 5% by weight of the honeycomb precursor composition mixture. When used, the oil may not be miscible with water, so that it forms a stable emulsion with any liquid polymer resin. Some exemplary oils that can be used include petroleum with a molecular weight of about 250 to 1000kg / mole, containing paraffinic and / or aromatic and / or alicyclic compounds. When using paraffin oils mainly including paraffinic and alicyclic structures, these can contain additives, such as rust inhibitors or antioxidants, such as they are generally present in commercially available oils. Some available oils are 3M's three-in-one oils, or three-in-one household oils of Reckitt and Coleman Inc., of Wayne, New Jersey. Other available oils can include: synthetic oils based on polyalphaolefins, esters, polyalkylene glycols, polybutenes, silicones, polyphenylene oxides, CTFE oils, and other commercially available oils. Vegetable oils such as sunflower oil, sesame oil, peanut oil, etc. can also be used. These oils can have a viscosity of about 10 to 300 centipoise. Generally speaking, the amount of activated carbon in the formed body is about 10% to 98% by weight.
[0044] In order to obtain the desired pore structure, an optional pore former can be incorporated into the honeycomb precursor composition. In some embodiments, the pore former may include polypropylene, polyester or acrylic powder or fiber, which leaves little or no residue after decomposition in an inert atmosphere at high temperature (>400°C). In some embodiments, the pore former forms macropores due to particle expansion. For example, intercalated graphite containing acids such as hydrochloric acid, sulfuric acid or nitric acid may form macropores when heated due to acid-induced expansion. In addition, macropores can also be formed by dissolving certain fugitive materials. For example, baking soda, calcium carbonate or limestone particles with a particle size corresponding to the desired pore size can be extruded with a carbonaceous material to form a honeycomb green body. Baking soda, calcium carbonate or limestone forms water-soluble oxides during the carbonization and activation process, which can subsequently be leached to form macropores by soaking the honeycomb filter 100 in water.
[0045] The honeycomb precursor composition can be formed to provide a honeycomb having a plurality of parallel cell channels 108, which are defined by porous channel walls 106 that traverse the honeycomb from the upstream inlet end 102 to the downstream outlet end 104. The precursor composition can be formed at various stages of the method for forming the honeycomb filter 100 described herein, including: before the heat treatment and / or activation of the precursor composition, after the heat treatment of the precursor composition but before the activation of the precursor composition, and after the heat treatment and activation of the precursor composition. The precursor composition can be formed by any known conventional process, such as extrusion, injection molding, slide casting, centrifugal casting, pressure casting, and dry pressing. In one embodiment, extrusion can be accomplished using a hydraulic ram extruder, a dual-stage exhaust single screw extruder, or a twin-screw mixer (a die assembly is attached to the discharge end). When a twin-screw mixer is used, appropriate screw elements can be selected according to the material and other process conditions to accumulate sufficient pressure to force the precursor composition material through the die.
[0046] Thermally treating the shaped or unshaped precursor composition may include subjecting the shaped or unshaped precursor composition to thermal treatment conditions sufficient to cure and / or carbonize any crosslinked resin component present in the precursor composition. Curing is typically performed in air at atmospheric pressure and typically by heating the shaped or unshaped precursor composition at a temperature of about 100° C. to about 200° C. for about 0.5 to about 5.0 hours. Alternatively, with certain precursors (e.g., furfuryl alcohol), curing may also be accomplished by adding a curing catalyst (e.g., an acid catalyst) at room temperature.
[0047] Carbonization refers to the thermal decomposition of carbonaceous materials, thereby eliminating low molecular weight species (e.g., carbon dioxide, water, gaseous hydrocarbons, etc.) and producing a fixed carbon mass and a preliminary pore structure in the carbon. Such transformation or carbonization of the crosslinked resin is generally accomplished by heating to a temperature range of about 600° C. to about 1200° C. for about 1 to 10 hours in a reducing or inert atmosphere (e.g., nitrogen, argon, helium, etc.). Carbonization of the crosslinked resin can result in substantially uninterrupted carbon.
[0048] The carbonized honeycomb can then be heat treated to activate the carbon and produce an activated carbon structure. Activation can be done to enhance the volume and enlarge the diameter of the macropores formed during the carbonization process and to produce new porosity. Activation can produce a high surface area and thereby impart a high adsorption capacity to the structure. Activation can be done by known methods, such as exposing the structure to a high temperature (e.g., about 600° C. to about 1000° C.) oxidant, such as steam, carbon dioxide, metal chlorides (e.g., zinc chloride), potassium hydroxide, phosphoric acid, or sulfuric acid.
[0049] In order to provide a wall-flow configuration as described herein, the method of the present disclosure may further include selectively plugging at least one predetermined cell channel end with a plugging material to form a selectively plugged honeycomb structure. Selective plugging may be performed before carbonization of the honeycomb precursor composition, or alternatively after completion of the carbonization process or activation process. In one or more embodiments, the plugging material may be selected from those having a similar shrinkage rate to the honeycomb during the carbonization process. Examples may include the same or similar honeycomb precursor composition used to form a honeycomb body, or a slightly modified composition comprising one or more synthetic cross-linked resins. In one or more embodiments, any material capable of sealing the cell channel 108 and maintaining the desired application temperature (e.g., 150°C to 300°C) may be used. Examples may include: UV-curable or heat-curable polymer resins, such as phenolic resins or epoxy resins, heat-curable inorganic pastes, such as Al2O3, SiO2, TiO2, ZrO2 or mixtures thereof, inorganic-organic hybrid materials (which contain one or more UV-curable or heat-curable polymers and one or more inorganic compositions, such as Al2O3, SiO2, TiO2, ZrO2, Si, SiC or carbon fibers). In addition, a pore channel size matching solid with a heat-curable binder may also be used as a post-carbonization or activated processing material. The solid may be selected from materials that can maintain the desired application temperature (e.g., 150°C to 300°C), such as glass, wood and polymers. The binder may also be any material or combination of materials mentioned above for plugging without a pore channel size matching solid.
[0050] To complete the plugging process, a certain amount of plugging material can be distributed into the desired cell channel 108 with a syringe. In another embodiment, a mask can be used to alternately cover or block the selective honeycomb cell channel 108 and allow the plugging material to spread into the end of the unmasked or uncovered channel. Syringe plugging and mask spreading plugging can be completed manually or using automated facilities. In one embodiment, the viscosity of the plugging material can be adjusted to a range of 400cP to 5000cP to achieve distribution or spreading.
[0051] It will now be appreciated that honeycomb filters having activated carbon containing at least 1 wt % nitrogen can have enhanced performance characteristics, particularly for carbon dioxide filtration and capture.
[0052] Example
[0053] The examples provided herein may disclose one or more embodiments of the present disclosure. However, the examples should not be considered as limitations on the claimed embodiments provided above.
[0054] Example 1: Synthesis of Carbonized Aminophenol Resin
[0055] Under alkaline conditions, aminophenol resin is prepared using methanol or water as a solvent, as shown in the following chemical formula A.
[0056] Chemical Formula A
[0057]
[0058] The ratio of aminophenol to formaldehyde used was 1:2. The mixture was heated to 75°C for 2 hours. The resulting resin was then crosslinked at 150°C. The crosslinked aminophenol resin was carbonized at 1000°C for 2 hours in a nitrogen atmosphere. The carbonized carbon was further ground to a particle size of 5 μm. Table 1 below lists the crosslinking and carbonization yields of aminophenol formaldehyde resins synthesized using methanol and water as solvents. Table 2 below shows the carbon, hydrogen and nitrogen composition data of the aminophenol formaldehyde resins formed.
[0059] Table 1
[0060]
[0061] Table 2
[0062] Sample name Carbon (wt%) Hydrogen (wt%) Nitrogen (wt%) 3-Aminophenol formaldehyde in water 59.51 1.11 8.41 4-Aminophenol formaldehyde in water 51.46 1.13 11.41 3-Aminophenol formaldehyde in MeOH 75.85 1.43 9.52 4-Aminophenol formaldehyde in MeOH 90.85 1.05 3.56
[0063] Example 2: Synthesis of Carbonized Melamine Formaldehyde Resin
[0064] Melamine formaldehyde resin was synthesized according to the following chemical formula B.
[0065] Chemical Formula B
[0066]
[0067] The ratio of melamine to formaldehyde used to form the melamine formaldehyde resin was 1:2. The mixture of melamine and formaldehyde was slowly heated to 75°C to start the condensation reaction. The pH of the reaction mixture was maintained at 9 to avoid any crosslinking reaction under acidic conditions. The reaction mixture was stirred at 75°C and pH 9 for 2 hours. A significant thickening of the reaction mixture was observed, which indicated the progress of the condensation reaction. The condensation reaction of melamine and formaldehyde is shown below.
[0068] In the presence of p-toluenesulfonic acid (PTSA) as a catalyst, the synthesized melamine formaldehyde resin crosslinked (cured) at 176° C. The yields of melamine formaldehyde resin after curing and carbonization are listed in Table 3 below.
[0069] Table 3
[0070]
[0071] The carbon prepared with melamine formaldehyde resin having 0.02 mol PTSA / kg resin showed the highest carbon yield after carbonization (42% ± 0.6%). The cross-linked resin was carbonized at 1000°C under nitrogen. The carbonized carbon was further ground to 5 μm particle size. The carbon was analyzed using elemental analysis as shown in Table 4 below.
[0072] Table 4
[0073]
[0074] Various grades of melamine formaldehyde resins were obtained from Hexion Specialty Chemicals. The resin details are listed in Table 5 below. The different viscosities and percent solids show that the resin synthesis processes were different.
[0075] Table 5
[0076] Hexion Melamine Formaldehyde Resin Viscosity(cP) Solid percentage Storage life Astro Mel NW 3A 600 80 4-6 months Astro Mel 400 1000 82 6 months to 1 year Astro Mel 601 4000-5000 100 More than 1 year
[0077] The three different resins were optimized for crosslinking conditions (temperature and PTSA concentration) and subsequent carbonization. PTSA was added to the resin and stirred for 5 minutes, after which the resin was placed in an oven at the specified temperature for crosslinking. The catalyst PTSA concentration and curing temperature were optimized for these resins in the PTSA concentration range of 0 to 0.04 mol / kg, and the temperature range evaluated was 150-200°C. The Hexion crosslinked resin was carbonized at 1000°C for 2 hours under a nitrogen atmosphere and ground to a particle size of 5um. The optimized Hexion NW 3A resin gave the following best yields: 64% ± 0.7% after crosslinking at 176°C (0.02 mol / kg PTSA), and 29% ± 2% after carbonization. Table 6 below gives comparative data for the three Hexion resins.
[0078] Table 6
[0079]
[0080] Elemental analysis was performed to analyze the carbon, hydrogen and nitrogen contents as shown in Table 7.
[0081] Table 7
[0082]
[0083] Example 3: Activation of carbon materials
[0084] 5 grams of carbonized carbon were mixed with 10 grams of potassium hydroxide (KOH) in a silicon carbide crucible. The carbonized carbon-KOH mixture was then placed in a distillation furnace. The furnace was flushed with nitrogen gas (flow rate was about 62 L / min). The furnace was then heated to 900°C at 200°C / min and maintained at 900°C for 4 hours under a nitrogen atmosphere. The furnace was then cooled at the furnace rate. The resulting activated carbon was then washed with water to a neutral pH (7). Table 8 below gives the percentage activation of carbon after KOH activation for different precursors.
[0085] Table 8
[0086]
[0087] Example 4: Testing CO2 adsorption of activated carbon materials
[0088] Table 9 below gives the surface area and pore volume data of various activated carbons as well as CO2 adsorption data.
[0089] Table 9
[0090]
[0091] The present disclosure includes one or more non-limiting aspects. A first aspect includes a honeycomb filter comprising a porous honeycomb body containing activated carbon, the porous honeycomb body having a plurality of parallel cell channels defined by porous channel walls that traverse the porous honeycomb body from an upstream inlet end to a downstream outlet end, wherein: the activated carbon is distributed throughout the porous channel walls; and the activated carbon comprises 1 wt % to 50 wt % nitrogen, based on the total weight of the activated carbon.
[0092] A second aspect includes any of the above aspects, wherein the activated carbon comprises 10 wt % to 50 wt % nitrogen, based on the total weight of the activated carbon.
[0093] A third aspect includes any of the above aspects, wherein the activated carbon comprises 15 wt % to 50 wt % nitrogen, based on the total weight of the activated carbon.
[0094] A fourth aspect includes any of the above aspects, wherein the activated carbon comprises 20 wt % to 50 wt % nitrogen, based on the total weight of the activated carbon.
[0095] A fifth aspect includes any of the above aspects, wherein the activated carbon is formed by processing of a cross-linked resin.
[0096] Aspect 6 includes any of the above aspects, wherein one or more parallel cell channels contain end plugs to seal the porous channel walls defining the one or more cell channels, thereby forming one or more parallel cell channels with their ends plugged.
[0097] A seventh aspect includes any of the above aspects, wherein the porous honeycomb body further comprises an inorganic filler.
[0098] Aspect 8 includes a method for adsorbing carbon dioxide, which includes: allowing a gas containing carbon dioxide to pass through one or more of the multiple parallel channel pores of the honeycomb filter of any of the above aspects, wherein at least a portion of the gas passes through one or more of the porous channel walls, and at least a portion of the carbon dioxide from the gas is adsorbed onto the one or more porous channel walls.
[0099] A ninth aspect includes a method for manufacturing a honeycomb filter, the method comprising: forming a formable honeycomb precursor composition comprising a cross-linked resin, wherein the cross-linked resin comprises 0.5 wt % to 4 wt % nitrogen, based on the total weight of the cross-linked resin; forming the honeycomb precursor composition to form a honeycomb green body having a plurality of parallel cell channels defined by porous channel walls that traverse the honeycomb green body from an upstream inlet end to a downstream outlet end; heat treating the honeycomb green body to carbonize the cross-linked resin and form a carbonized honeycomb green body; and activating the carbonized honeycomb green body to produce a honeycomb filter, the honeycomb filter comprising an activated carbon honeycomb body having a plurality of parallel cell channels defined by porous channel walls that traverse the honeycomb body from an upstream inlet end to a downstream outlet end, wherein the activated carbon honeycomb body comprises activated carbon that comprises 1 wt % to 50 wt % nitrogen, based on the total weight of the activated carbon.
[0100] A tenth aspect includes any of the above aspects, wherein the cross-linking resin includes an aminophenol-based resin, a melamine-based resin, a nitrophenol-based resin, or a combination thereof.
[0101] An 11th aspect includes any of the above aspects, wherein the heat treatment of the honeycomb green body includes heating the honeycomb green body to a temperature of 600° C. to 1200° C. for 1 hour to 10 hours in an inert atmosphere.
[0102] A 12th aspect includes any of the above aspects, wherein activation of the carbonized honeycomb green body comprises contacting the carbonized honeycomb green body with an oxidant at a temperature of 600°C to 1000°C.
[0103] A 13th aspect includes any of the above aspects, wherein the oxidant comprises potassium hydroxide, carbon dioxide, steam, or a combination thereof.
[0104] A fourteenth aspect includes a honeycomb filter, wherein the honeycomb filter is synthesized by the method of any of the above aspects.
[0105] Aspect 15 includes a method for manufacturing a honeycomb filter, the method comprising: forming a honeycomb precursor composition comprising a cross-linked resin, wherein the cross-linked resin comprises 0.5 weight percent to 4 weight percent nitrogen, based on the total weight of the cross-linked resin; heat-treating the honeycomb precursor composition to carbonize the cross-linked resin and form a carbonized honeycomb precursor composition; activating the carbonized honeycomb precursor composition to produce an activated honeycomb precursor composition; and forming the activated honeycomb precursor composition to form a honeycomb filter, the honeycomb filter comprising an activated carbon honeycomb body having a plurality of parallel cell channels defined by porous channel walls that traverse the honeycomb body from an upstream inlet end to a downstream outlet end, wherein the activated carbon honeycomb body comprises activated carbon comprising 1 weight percent to 50 weight percent nitrogen, based on the total weight of the activated carbon.
[0106] A sixteenth aspect includes any of the above aspects, wherein the cross-linking resin is an aminophenol-based resin, a melamine-based resin, a nitrophenol-based resin, or a combination thereof.
[0107] A 17th aspect includes any of the above aspects, wherein the heat treatment of the honeycomb precursor composition comprises heating the honeycomb precursor composition to a temperature of 600° C. to 1200° C. for 1 hour to 10 hours in an inert atmosphere.
[0108] An eighteenth aspect includes any of the above aspects, wherein the activation of the carbonized honeycomb precursor composition comprises contacting the carbonized honeycomb precursor composition with an oxidant at a temperature of 600°C to 1000°C.
[0109] A 19th aspect includes any of the above aspects, wherein the oxidant comprises potassium hydroxide, carbon dioxide, steam, or a combination thereof.
[0110] A twentieth aspect includes a honeycomb filter, wherein the honeycomb filter is synthesized by the method of any of the above aspects.
[0111] The subject matter of the present disclosure has been described in detail and with reference to specific embodiments. It should be understood that any specific description of a component or feature of an embodiment does not necessarily imply that the component or feature is essential to that particular embodiment or any other embodiment. In addition, it will be apparent to those skilled in the art that various modifications and variations may be made to the embodiments without departing from the spirit and scope of the subject matter for which the patent right is claimed.
[0112] It is noted that one or more of the following claims use the term "wherein" as a transitional phrase. For the purpose of defining the technology herein, it should be noted that this term is used in the claims as an open transitional phrase to introduce a description of a series of structural features, and should be interpreted similarly to the more commonly used open introductory phrase "including".
[0113] It should be understood that when a first component is described as "comprising" a second component, it is contemplated that in some embodiments, the first component is "consisting of" or "consisting essentially of" the second component. It should also be understood that when a first component is described as "comprising" a second component, it is contemplated that in some embodiments, the first component contains at least 10%, at least 20%, at least 30%, at least 40%, at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 95%, or even at least 99% of the second component (wherein % may be wt% or mole%).
[0114] For the purpose of describing and defining the present technology, it is noted that references herein to a variable being a "function" of a parameter or another variable are not intended to mean that the variable is a function of only the listed parameter or variable. Rather, references herein to a variable being a "function" of the listed parameters are open ended, such that the variable may be a function of a single parameter or multiple parameters.
[0115] It should also be noted that the reference to “at least one” of a component, element, etc. herein should not be construed as limiting the optional use of the modifiers “a” or “an” to a single component, element, etc.
[0116] It should be understood that any two magnitudes assigned to a property may constitute a range for that property, and that all combinations of ranges formed by all specified magnitudes for a given property are contemplated herein.
Claims
1. A honeycomb filter, comprising: A porous honeycomb body comprising activated carbon, the porous honeycomb body having a plurality of parallel cell channels defined by porous channel walls extending across the porous honeycomb body from an upstream inlet end to a downstream outlet end, wherein: The activated carbon is distributed throughout the porous channel walls; and The activated carbon contains 1% to 50% by weight of nitrogen, based on the total weight of the activated carbon.
2. The honeycomb filter according to claim 1, wherein The activated carbon contains 10% to 50% by weight of nitrogen, based on the total weight of the activated carbon.
3. The honeycomb filter according to claim 1, wherein The activated carbon contains 15% to 50% by weight of nitrogen, based on the total weight of the activated carbon.
4. The honeycomb filter according to claim 1, wherein The activated carbon contains 20% to 50% by weight of nitrogen, based on the total weight of the activated carbon.
5. The honeycomb filter according to claim 1, wherein Activated carbon is formed by the processing of cross-linked resins.
6. The honeycomb filter according to any one of claims 1 to 5, wherein: One or more parallel cell channels include end plugs to seal the porous channel walls defining the one or more cell channels, thereby forming one or more parallel cell channels with their ends plugged.
7. The honeycomb filter according to any one of claims 1 to 6, wherein: The porous honeycomb body also contains an inorganic filler.
8. A method for adsorbing carbon dioxide, the method comprising: A gas containing carbon dioxide is allowed to pass through one or more of the plurality of parallel channel pores of the honeycomb filter as described in claim 1, wherein at least a portion of the gas passes through one or more of the porous channel walls, and at least a portion of the carbon dioxide from the gas is adsorbed onto the one or more porous channel walls.
9. A method for manufacturing a honeycomb filter, the method comprising: forming a formable honeycomb precursor composition comprising a crosslinked resin, wherein the crosslinked resin comprises 0.5 wt % to 4 wt % nitrogen, based on the total weight of the crosslinked resin; forming a honeycomb precursor composition to form a honeycomb green body having a plurality of parallel cell channels defined by porous channel walls extending across the honeycomb green body from an upstream inlet end to a downstream outlet end; heat-treating the honeycomb green body to carbonize the cross-linked resin and form a carbonized honeycomb green body; and activating the carbonized honeycomb green body to produce a honeycomb filter comprising an activated carbon honeycomb body having a plurality of parallel cell channels defined by porous channel walls extending across the honeycomb body from an upstream inlet end to a downstream outlet end, The activated carbon honeycomb body contains activated carbon, and the activated carbon contains 1 wt % to 50 wt % of nitrogen, based on the total weight of the activated carbon.
10. The method of claim 9, wherein: The cross-linking resin includes an aminophenol-based resin, a melamine-based resin, a nitrophenol-based resin, or a combination thereof.
11. The method according to claim 9 or 10, wherein: The heat treatment of the honeycomb green body includes heating the honeycomb green body to a temperature of 600° C. to 1200° C. for 1 hour to 10 hours in an inert atmosphere.
12. The method according to any one of claims 9 to 11, wherein: Activation of the carbonized honeycomb green body includes contacting the carbonized honeycomb green body with an oxidant at a temperature of 600°C to 1000°C.
13. The method of claim 12, wherein: The oxidizing agent includes potassium hydroxide, carbon dioxide, steam, or a combination thereof.
14. A honeycomb filter, wherein: The honeycomb filter is synthesized by the method according to claim 9.
15. A method for manufacturing a honeycomb filter, the method comprising: forming a honeycomb precursor composition comprising a crosslinked resin, wherein the crosslinked resin comprises 0.5 wt % to 4 wt % nitrogen, based on the total weight of the crosslinked resin; heat treating the honeycomb precursor composition to carbonize the crosslinked resin and form a carbonized honeycomb precursor composition; activating the carbonized honeycomb precursor composition to produce an activated honeycomb precursor composition; and shaping the activated honeycomb precursor composition to form a honeycomb filter comprising an activated carbon honeycomb body having a plurality of parallel cell channels defined by porous channel walls extending across the honeycomb body from an upstream inlet end to a downstream outlet end, The activated carbon honeycomb body contains activated carbon, and the activated carbon contains 1 wt % to 50 wt % of nitrogen, based on the total weight of the activated carbon.
16. The method of claim 15, wherein: The cross-linking resin is an aminophenol-based resin, a melamine-based resin, a nitrophenol-based resin, or a combination thereof.
17. The method according to claim 15 or 16, wherein: The heat treatment of the honeycomb precursor composition includes heating the honeycomb precursor composition to a temperature of 600° C. to 1200° C. for 1 hour to 10 hours in an inert atmosphere.
18. The method according to any one of claims 15 to 17, wherein: Activation of the carbonized honeycomb precursor composition includes contacting the carbonized honeycomb precursor composition with an oxidant at a temperature of 600°C to 1000°C.
19. The method of claim 18, wherein: The oxidizing agent includes potassium hydroxide, carbon dioxide, steam, or a combination thereof.
20. A honeycomb filter, wherein: The honeycomb filter is synthesized by the method described in any one of claims 15-19.
Citation Information
Patent Citations
Extruded structures from thermosetting resins
US5820967A